The Relationship Between Play Patterns and the Development and Maturation of Children's Thinking Abilities (Cognitive) of Preschool Age in Kindergarten - Kasmiati, Kasmiati; M, Warda; Amalia, Rizki; Fitri, Lidia; Rahayu, Rahayu (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The function of play and interaction in games has an important role in children's cognitive and social development. Playing gives a relaxing effect to children. The purpose of this study was to determine the relationship between playing patterns and the cognitive development of preschool children. This research method is a quantitative study with a survey analysis research design with a cross-sectional study approach. The sampling technique used was a total sampling of 30 students. The instrument used was a questionnaire sheet. The results of the analysis of the relationship between play patterns and cognitive development showed that there was a relationship between play patterns and cognitive development, this was based on the results of the chi square test showing that α <0.05 with a value of α = 0.033. The conclusion of this study There is a relationship between play patterns and cognitive development in Kindergarten.